EFEKTIVITAS SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) PADA DINAS PERTANIAN DAN PANGAN KOTA MAGELANG - Ricky Mukaromah; Nuwun Priyono (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this study was to determine the effectiveness of the Government Agency Performance Accountability System (SAKIP) and to find out the supporting and inhibiting factors for the implementation of SAKIP's effectiveness in the Dinas Pertanian dan Pangan Kota Magelang. This research use desciptive qualitative approach. Data collection techniques using interviews, observation, and documentation. The results of this study indicate that SAKIP in the Dinas Pertanian dan Pangan Kota Magelang has been running effectively. The implementation of SAKIP in the Dinas Pertanian dan Pangan Kota Magelang has increased every year which can be seen from the level of success of the work programs that have been implemented.